Early Evolution of Himalayan Orogenic Belt and Generation of Middle Eocene Magmatism: Constraint From Haweng Granodiorite Porphyry in the Tethyan Himalaya - Ji, Wei-Qiang; Wu, Fu-Yuan; Wang, Jia-Min; Liu, Xiao-Chi; Liu, Zhi-Chao; Zhang, Zhiyong; Cao, Wenrong; Wang, Jian-Gang; Zhang, Chang (Frontiers in Earth Science, 2020)
Although the Himalayan orogenic belt is dominant by Oligocene to Miocene leucogranites, it initiated magmatic activity from middle Eocene. However, the exact distribution and genesis of early magmatism are yet to be resolved. This study identified new outcrops of middle Eocene magmatism, Haweng granodiorite porphyries, from northwest Langkazi in the northern Tethyan Himalaya, southern Tibet. Identical zircon U–Pb ages were obtained by secondary ion mass spectrometry (17JT13: 45.3 ± 0.4 Ma; 17JT16: 44.5 ± 0.8 Ma) and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) (17JT15: 44.3 ± 0.8 Ma; 12FW75: 44.4 ± 0.6 Ma) methods for different outcrops there. Titanite LA-ICP-MS U–Pb analyses also gave consistent lower intercept ages for samples 17JT13 (45.3 ± 0.5 Ma) and 17JT15 (44.5 ± 0.6 Ma). Zircon metamorphic rims of sample 17JT15 recorded a younger thermal event of 29.9 ± 0.4 Ma. The analyzed samples possess high SiO2 (69.98–73.53 wt.%), Al2O3 (15.07–16.15 wt.%), variable Na2O (3.94–5.81 wt.%) with Na2O/K2O ratios of 1.57–7.88, and A/CNK values of 1.08–1.27 indicative of sodic peraluminous series. They show variable Sr (342–481 ppm) and Rb (37.9–133 ppm) concentrations and low Rb/Sr ratios (0.10–0.39), radiogenic Sr isotopes [87Sr/86Sr(t): 0.7190–0.7251], and unradiogenic Nd–Hf isotopes with εNd(t) values of −13.54 to −11.55 and εHf(t) values of −11.97 to −9.37, respectively. The variation of major and trace elements, such as increases in Na2O and Sr and decreases in K2O and Rb, resulted from cumulation of plagioclase and crystal fractionation of K-feldspar during magma evolution. The Haweng granodiorite porphyries were derived from partial melting of dominant amphibolites and variable metasedimentary rocks. The newly identified outcrops help conform the EW trending middle Eocene magmatic belt along the Yarlung Tsangpo suture zone, resulting from breakoff of the Neo-Tethyan slab at ca. 45 Ma.